(3EfSGf GdYjhf aj SjQI GdCejf hGdeCehfs - (3GHf GdHfGA , fhQ GdOjf CHh GdaQL Ydj Hf EHQGgje Hf CMeO GdMdHj, fhQ GdOjf GdMdHj,J (B1044 (3g` s
(3ChdgG (B:s
(3bGd Udi Gddg Ydjg hSde GdChdjI hgj KdGKI s
(3BNQgG (B:s
(3ajeG Hjf HGH GdQMeI Edi HGH GdCSHGW Je s
(3HgG fXGe GdJYbjHIs
(3LRA ef GdcJGHs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B54s
Keywords: (3GdJGQjNs